Spontaneous genetic damage in the tegu lizard (Tupinambis merianae): The effect of age - Schaumburg, Laura Gisela (2014)
Several studies indicate that certain factors such as age, sex or nutritional status among others, mayaffect the level of DNA damage, both induced and spontaneous, so it is very important to consider themfor a more accurate interpretation of the findings. The aim of this study was to analyze the influenceof age, sex, and nest of origin on spontaneous genetic damage of Tupinambis merianae determined bythe comet assay (CA) and the micronucleus (MN) test, in order to improve reference data for futurein vivo studies of xenobiotics exposure in this species. Sixty-five tegu lizards of three different ages:newborns (NB), juveniles (JUV) and adults (AD), both sexes and from different nests of origin were used.Blood samples were collected from the caudal vein of all animals and the MN test and CA were appliedon peripheral blood erythrocytes to determine basal frequency of MN (BFMN) and basal damage index(BDI). The comparison between age groups showed statistically significant differences in the BFMN andBDI (p < 0.05). NB animals showed significantly higher BDI values in relation to JUV and AD (p < 0.016), butno statistically differences were found between the latter two. NB showed lower BFMN respect to otherage groups, being statistically significant only when compared to AD (p < 0.016). BFMN or BDI showed nostatistically significant differences between sexes or nests of origin (p > 0.05). A weak negative relationshipwas found only between BFMN and weight of NB tegu lizard (p = 0.014; R2= 0.245). Basal values of geneticdamage obtained with both biomarkers in the tegu lizard evidenced that age is an intrinsic factor thatshould be taken into account to avoid misunderstanding of the results in future biomonitoring studies.